Humanitarianism From Below: Border Police, Professional Identities and Moral Dilemmas - Aliverti, Ana (The British journal of criminology, 2025)
In this article, we empirically document the changing dynamics of border controls in the context of the COVID pandemic, and its consequences for border control workers, particularly police, border agents and the military. We focus on three areas: the Anglo-French (Dover-Calais) maritime border, the Euro-African border (Ceuta-Tetuán) and the South American border of Tarapacá-Oruro between Chile and Bolivia. We explore how sovereign strategies of containment and closure, and the diplomatic tensions that arise from them, sometimes operate uneasily with on-the-ground attempts to save lives and provide care in the most precarious situations. These competing institutional demands and moral and professional tensions and dilemmas, we argue, shape an emerging form of management of social precarity that we conceptualize as ‘humanitarianism from below’.